2022
DOI: 10.7717/peerj.12789
|View full text |Cite
|
Sign up to set email alerts
|

The value of diffusion weighted imaging-alberta stroke program early CT score in predicting stroke-associated pneumonia in patients with acute cerebral infarction: a retrospective study

Abstract: Background In this study, we aimed to investigate the value of Diffusion-Weighted Imaging-Alberta Stroke Program Early CT Score (DWI-ASPECTS) in predicting stroke-associated pneumonia (SAP) in patients with acute ischemic stroke. Methods A total of 291 patients who suffered acute cerebral infarction for the first time were included in this retrospective study. DWI-ASPECTS was assessed and clinical data were collected in order to find the ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 37 publications
1
3
1
Order By: Relevance
“…The diagnostic accuracy, specificity, and sensitivity of DWI for HICH and HCI were significantly higher than those of routine MRI, with differences of statistical significance ( P < 0.05). This was similar to the findings of Zhao et al [ 29 ], suggesting that DWI could better show the functional and physiological changes of water molecules in human tissues. Therefore, DWI was superior to routine MRI in the detection of both the diseases.…”
Section: Discussionsupporting
confidence: 91%
“…The diagnostic accuracy, specificity, and sensitivity of DWI for HICH and HCI were significantly higher than those of routine MRI, with differences of statistical significance ( P < 0.05). This was similar to the findings of Zhao et al [ 29 ], suggesting that DWI could better show the functional and physiological changes of water molecules in human tissues. Therefore, DWI was superior to routine MRI in the detection of both the diseases.…”
Section: Discussionsupporting
confidence: 91%
“…In our study, the AuROC of 24-h ASPECTS for predicting SAP was 0.84 (95% CI, 0.79-0.89). This differs from a previous study that evaluated the use of diffusion-weighted imaging-ASPECTS (DWI-ASPECTS) for SAP prediction (AuROC = 0.74 [95% CI, 0.68-0.80]) (24). Several factors may account for the differences.…”
Section: Discussioncontrasting
confidence: 81%
“…It has been confirmed by several studies that brain MRI-based imaging features are closely related to SAP. Zhao et al [ 43 ] showed that the DWI Alberta Stroke Program Early Computed Tomography Score (DWI-ASPECTS) used to predict the severity of AIS could also be used to predict the occurrence of SAP in patients with mild AIS [ 1 , 44 ]. We investigated the association between radiomics scores, infarct volumes and NIHSS scores, found that there was a linear positive correlation between radiomics scores and NIHSS scores (Pearson:0.171, P = 0.014), as well as between radiomics scores and infarct volume (Pearson:0.372, P < 0.001).…”
Section: Discussionmentioning
confidence: 99%